Association of Platelet Desialylation and Circulating Follicular Helper T Cells in Patients With Thrombocytopenia - Chen, Yuwen; Luo, Liping; Zheng, Yongzhi; Zheng, Qiaoyun; Zhang, Na; Gan, Donghui; Yirga, Shimuye Kalayu; Lin, Zhenxing; Shi, Qizhen; Fu, Lin; Hu, Jianda; Chen, Yingyu (Frontiers in Immunology, 2022)
Thrombocytopenia is a multifactorial condition that frequently involves concomitant defects in platelet production and clearance. The physiopathology of low platelet count in thrombocytopenia remains unclear. Sialylation on platelet membrane glycoprotein and follicular helper T cells (TFHs) are thought to be the novel platelet clearance pathways. The aim of this study was to clarify the roles of platelet desialylation and circulating TFHs in patients with immune thrombocytopenia (ITP) and non-ITP thrombocytopenia. We enrolled 190 patients with ITP and 94 patients with non-ITP related thrombocytopenia including case of aplastic anemia (AA) and myelodysplastic syndromes (MDS). One hundred and ten healthy volunteers were included as control. We found significantly increased desialylated platelets in patients with ITP or thrombocytopenia in the context of AA and MDS. Platelet desialylation was negatively correlated with platelet count. Meanwhile, the circulating TFH levels in patients with thrombocytopenia were significantly higher than those of normal controls, and were positively correlated with desialylated platelet levels. Moreover, TFHs-related chemokine CXCL13 and apoptotic platelet levels were abnormally high in ITP patients. The upregulation of pro-apoptotic proteins and the activation of the MAPK/mTOR pathway were observed in the same cohort. These findings suggested that platelet desialylation and circulating TFHs may become the potential biomarkers for evaluating the disease process associated with thrombocytopenia in patients with ITP and non-ITP.